FAMILIES RESILIENCE WITH RECOVERY ADDICT IN SUMEDANG UTARA DISTRICT SUMEDANG REGENCY INDONESIA - Atirista Nainggolan (Politeknik Kesejahteraan Sosial Bandung, 2022)
This research is motivated by substance abuse in Indonesia worrying increasingly year by year. Substance abuse is a threat to Indonesia, especially at a productive age, and affects family resilience. The family resilience of recovery addict is the family in facing all living conditions to achieve an independent life and improve family welfare. Research on